Factors for Value Realization of Tomato, Onion, and Potato (TOP) under Operation Greens Using DEMATEL Method - Praveen Kumar; Kumbhare, Narayan Vithoba; Manjeet Singh Nain; Sitaram Bishnoi; Ankur Biswas; Pramod Kumar; Shiv Prasad (Indian Journal of Extension Education, 2023)
Operation Greens Programme of the Government of India focuses on post-harvest management of Tomato, Onion, and Potato (TOP) crops, value chain development, and value realization of farmers’ produce, which helps in enhancing livelihood security. The study conducted during 2022-2023 focused on factors determining the value realization of TOP crops under operation greens. The data were collected using a semi-structured interview schedule, with 90 farmers for each crop i.e., Tomato, Onion, and Potato. The government policy initiatives under Operation Greens were the most important factor, which mutually affected the socio-psychological, market intelligence, and input supply for TOP cultivation. About 42% of respondents perceived Government policy under operation greens as important for value realization and 37.40% of respondents perceived support from grassroots level extension agencies as important. Improving government policies followed for Operation Greens would result in the overall betterment of farmers and the agricultural sector of India.